2020
DOI: 10.3839/jabc.2020.036
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation characteristics of mandipropamid and thiamethoxam for establishment of pre-harvest residue limits in lettuce

Abstract: The dissipation characteristics and kinetics of fungicide mandipropamid and insecticide thiamethoxam in lettuce under greenhouse conditions were investigated at three different lettucegrowing fields for estimating the pre-harvest residue limits (PHRLs). The analytical methods were fully validated for the quantitation of pesticide residues using High-Performance Liquid Chromatography-Photo Diode Array detector or Ultraviolet-Visible Detector and applied to real samples. The lettuces suitable for shipment were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
2
Order By: Relevance
“…농산물에 대한 잔류농약 검사는 수확 후나 유통단계에서 이뤄지는데, 기 준을 초과하여 부적합 판정을 받은 농산물의 경우 폐기처분 되 어 생산자인 농민에게 막대한 경제적 손실이 발생할 수 있다 [2]. 또한, 전수조사의 어려움으로 안전성 평가에서 누락되는 엽 채류와 같은 신선농산물이 많아 이 것들이 유통될 경우 위해성 을 초래할 수 있다 [3,6]. 이에 식품의약품안전처에서는 농산물의 사전 예방적 안전관 리를 위하여 작물 수확 시 잔류량이 MRL을 초과하지 않도록 생산단계 잔류허용기준(Pre-Harvest Residue Limit, PHRL)을 추 가로 설정하고 있다.…”
Section: 서 론unclassified
See 1 more Smart Citation
“…농산물에 대한 잔류농약 검사는 수확 후나 유통단계에서 이뤄지는데, 기 준을 초과하여 부적합 판정을 받은 농산물의 경우 폐기처분 되 어 생산자인 농민에게 막대한 경제적 손실이 발생할 수 있다 [2]. 또한, 전수조사의 어려움으로 안전성 평가에서 누락되는 엽 채류와 같은 신선농산물이 많아 이 것들이 유통될 경우 위해성 을 초래할 수 있다 [3,6]. 이에 식품의약품안전처에서는 농산물의 사전 예방적 안전관 리를 위하여 작물 수확 시 잔류량이 MRL을 초과하지 않도록 생산단계 잔류허용기준(Pre-Harvest Residue Limit, PHRL)을 추 가로 설정하고 있다.…”
Section: 서 론unclassified
“…이에 식품의약품안전처에서는 농산물의 사전 예방적 안전관 리를 위하여 작물 수확 시 잔류량이 MRL을 초과하지 않도록 생산단계 잔류허용기준(Pre-Harvest Residue Limit, PHRL)을 추 가로 설정하고 있다. PHRL은 시간에 따른 잔류농약의 소실특 성을 토대로 출하예정일에서 출하 10일전까지 일자별 농약잔류 기준을 임의로 추정한 수치로 농약안전사용기준 및 MRL이 설 정되어 있는 농약 및 농산물에 한해 설정하고 있다 [6].…”
Section: 서 론unclassified
“…This result was different with the study [16] that thiamethoxam degraded more quickly in cowpea, with 1 day, approximately 48% of thiamethoxam residue dissipated from cowpea in Beijing, whereas in Anhui, 54% residue dissipation occurred within the same period. In the exponential decay study for dissipation of thiamethoxam and clothianidin in crop [16][17][18][19], it was reported that persistence of the thiamethoxam and clothianidin in crop could be affected by physicochemical properties of soil such as pH, organic matter, clay content, growth temperature, rain, humidity and light intensity may have also played a significant in thiamethoxam residue.…”
Section: Dissipation Of Thiamethoxam and Its Metabolite Clothianidin ...mentioning
confidence: 99%
“…At present, the methods for detecting residues of mandipropamid in sesame leaves (Farha et al, 2016) (Dong et al, 2020) are mainly high-performance liquid chromatography (HPLC) and HPCL-tandem mass spectrometry (MS/MS). Moreover, residual behaviour analysis and research on mandipropamid in grapes (Malhat and Abdallah, 2012), lettuce (Yang et al, 2020), and Cnidium (Dong et al, 2020)have been undertaken. However, there have been no systematic studies on the residual behaviour, degradation dynamics, and dietary risk assessment of mandipropamid in ginseng.…”
Section: Introductionmentioning
confidence: 99%